Analisis Pengelolaan Dana Bantuan Operasional Kesehatan (BOK) di Puskesmas Babo Kabupaten Teluk Bintuni - Yandry Pasule; Natalia Paranoan; Amson Padolo (ARZUSIN, 2025)
The main issue addressed in this study concerns the management of Bantuan Operasional Kesehatan (BOK) funds at Babo Community Health Center (Puskesmas Babo), Teluk Bintuni Regency, which are provided by the central government to support improvements in basic health services in accordance with the Minimum Service Standards (SPM). This study aims to analyze the BOK fund management process, encompassing the stages of planning, implementation, recording, and reporting. A qualitative approach was employed, utilizing data collection techniques including direct observation, in-depth interviews with key informants, and document analysis. The findings reveal that BOK fund management begins with the preparation of the Activity Proposal Plan (RUK), which is finalized into the Activity Implementation Plan (RPK) through a joint review process with the District Health Office and the Ministry of Health. Upon approval, fund disbursement follows the Fund Withdrawal Plan (RPD), verified by the District Health Office and the Regional Financial and Asset Management Agency (BPKAD). Financial transactions are systematically recorded, and reporting is carried out based on disbursement stages and coordinated with the District Health Office. The study concludes that BOK fund management at Puskesmas Babo has been implemented adequately, with appropriate targeting and alignment to health service priorities. The findings imply that transparent and accountable BOK fund management contributes to improved access and quality of basic health services and may serve as a replicable model for other community health centers.